Analysis of endocrine disruption effect of Roundup(®) in adrenal gland of male rats - Pandey, Aparamita (Toxicol Rep, 2015)
The effect of Roundup(®) on adrenal gland steroidogenesis and signaling pathway associated with steroid production was investigated. Doses of 10, 50, 100 and 250 mg/kg bw/d Roundup(®) were administered for two weeks to adult male rats. The 10 mg/kg bw/d dose which reduced circulatory corticosterone levels, but did not change food consumption and body weight, was selected for further study. The expression of cholesterol receptor (low density lipoprotein receptor), de novo cholesterol synthesis enzyme (3-hydroxy-3-methylglutaryl-coenzyme A synthase), hormone-sensitive lipase, steroidogenic acute regulatory protein (StAR) mRNA and phosphorylated form was decreased. Adrenocorticotropic hormone receptor (ACTH), melanocortin-2 receptor, expression was not changed but circulatory ACTH levels and adrenal cortex protein kinase A (PKA) activity were reduced. Surprisingly, exogenous ACTH treatment rescued steroidogenesis in Roundup(®)-treated animals. Apoptosis was evident at 250 mg/kg bw/d, but not at 10 mg/kg bw/d dose. These results suggest that Roundup(®) may be inhibitory to hypothalamic–pituitary axis leading to reduction in cyclic adenosine monophosphate (cAMP)/PKA pathway, StAR phosphorylation and corticosterone synthesis in the adrenal tissue.